Endoscopic Features of Patients with Bronchial Asthma and Gastroesophageal Reflux Symptoms - Syafruddin AR Lelosutan; Agus Dwi Susanto; Ruswhandi M (The Indonesian Society for Digestive Endoscopy, 2006)
Background: Studies evaluating endoscopic results in patients with bronchial asthma and Gastroesophageal Reflux Disease (GERD) in Gatot Soebroto hospital have never been undertaken. It leads an idea to further study, in order to find a more accurate and rapid management as solution for anticipating asthma attack and complications of bronchial asthma to upper gastrointestinal tract. Methods: A retrospective study was aimed to evaluate endoscopic result of upper gastrointestinal tract in bronchial asthma patients who had GERD symptoms as appropriate to the criteria of 4 major GERD symptoms of Talley 2002. Data was collected in one year period starting from November 2004 to October 2005. Results: Subject characteristics in this study indicated that there were more female patients compared to male with a ratio approaching 3:1 who had such symptoms. Mean age was 38.5 years and ratio of body weight to body height indicated normal weight result and the mean value for duration of asthma was 27 years. Clinical symptoms of GERD found in the present study was in accordance with four majors symptoms of GERD i.e. 32 (100.00%) cases of regurgitation, 29 (90.63%) cases for each of heartburn and non-cardiac chest pain symptom, and 7 (21.88%) cases of difficult / painful swallowing or dys/odinophagia. The endoscopic result of upper gastrointestinal tract had figured of: (1) 4 (12.50%) cases of normal esophagus, (2) 11 (34.40%) cases of non-erosive esophagitis known as Non Erosive Reflux Disease (NERD), and (3) erosive esophagitis which regarding to Los Angeles classification: 15 (46.90%) cases of grade A and 2 (6.20%) cases of grade B. Conclusion: The incidence of esophagitis in accordance with LA classification is extremely high although no severe damage (grade C and grade D) was found. Early anticipation of reflux associated respiratory symptoms and anti-reflux treatment should be considered in order to shorten or to discontinue the asthma attack cycle. Keywords: bronchial asthma, GERD, endoscopy, NERD